Wastewater surveillance for SARS-CoV-2 during a mass sporting event in the City of Cape Town, Western Cape - Nkambule, Sizwe; Street, Renée; Surujlal-Naicker, Swastika; Johnson, Rabia; Mathee, Angela (Frontiers in Public Health, 2024)
BackgroundWastewater surveillance has become an important public health tool with numerous research studies indicating its potential for monitoring coronavirus disease 2019 (COVID-19) outbreaks. The aim of this study was to apply wastewater surveillance as an indicator for COVID-19 to monitor the impact of a mass sporting event in the City of Cape Town. The study compared the same event over 2 years (2022 and 2023).MethodsWeekly grab wastewater samples were collected from wastewater treatment plants in the City of Cape Town, and quantitative reverse transcription-polymerase chain reaction used to quantify severe acute respiratory syndrome 2 (SARS-CoV-2) RNA in wastewater.ResultsOur findings show a statistically significant correlation (rho = 0.68, p = 0.01) between clinical cases and concentrations of SARS-CoV-2 RNA in wastewater in the 2022 study period. During this specific period, a rise in clinical cases was observed 2 weeks after the event and the peaks in clinical cases coincided with the peaks in SARS-CoV-2 RNA level in wastewater. The study also found a statistically significant positive correlation (R2 = 0.03, F (1,208) = 6.56, p = 0.01) between the SARS-CoV-2 RNA in wastewater and the 2022 event of the marathon hosted in the city.ConclusionDue to the decrease in clinical testing and the country being a popular destination for mass gatherings such as sporting events, the results from this study indicate the potential of wastewater surveillance providing supplementary information to form part of public health risk evaluations for mass gatherings.